1991
DOI: 10.1016/0033-5894(91)90024-y
|View full text |Cite
|
Sign up to set email alerts
|

Holocene deltaic sequence in the Saloum estuary, Senegal

Abstract: The 2250 km2 Saloum delta, south of Dakar, Senegal, consists of a Holocene sedimentary sequence deposited during five evolutionary stages: submerged postglacial ria, funnel-like estuary, barred estuary, cuspate delta, and reverse estuary. The passage from one stage to another was marked by the deposition of sedimentary units consisting of shelly sands, silty or sandy clays, and an extensive thick green mud. Muds in the lower strata, dating between 6130 and 3500 yr B.P., were deposited on a subtidal mudflat, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…However, these examples are atypical for deflected deltas, because much of the modern deltas of the Saloum and Senegal were built as bayhead deltas. The bays they grew in were protected by sandy spits formed of sediments eroded from updrift areas (Michel, 1968; Ausseil‐Badie et al ., 1991). Therefore, these spits were not necessarily deltaic before the bayhead deltas reached the open ocean, and these depositional systems bear more resemblance to the wave‐dominated estuaries of Dalrymple et al .…”
Section: Deflected Wave‐influenced Deltasmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these examples are atypical for deflected deltas, because much of the modern deltas of the Saloum and Senegal were built as bayhead deltas. The bays they grew in were protected by sandy spits formed of sediments eroded from updrift areas (Michel, 1968; Ausseil‐Badie et al ., 1991). Therefore, these spits were not necessarily deltaic before the bayhead deltas reached the open ocean, and these depositional systems bear more resemblance to the wave‐dominated estuaries of Dalrymple et al .…”
Section: Deflected Wave‐influenced Deltasmentioning
confidence: 99%
“…(A) Senegal delta, Senegal (after Michel, 1968). (B) Saloum delta, Senegal (after Ausseil‐Badie et al ., 1991). (C) Mahanadi delta, India (after Meijerink, 1982; Bharali et al ., 1991; Mohanti, 1993).…”
Section: Deflected Wave‐influenced Deltasmentioning
confidence: 99%
“…These two causes, which are moreover linked, seem to have played simultaneously in zone O of the Néma Ba core. The high sandy fraction in the lower part of the core is a known phenomenon in the first filling deposits of the Saloum estuary [8] . These authors indicated that between 6130 and 3500 years B.P.…”
Section: Discussionmentioning
confidence: 98%
“…The Saloum estuary has been the focus of several studies. They are based on the mangrove, its evolution and its deterioration [6,7] ; sedimentology [2,3,8,9] ; geomorphology, grain size, exoscopy and mineralogy [10,11] ; microfauna and macrofauna [12] ; salinity, rainfall and precipitation-evaporation [13][14][15][16] biology of fish community [17] and archaeology [4,18] . However, few studies have been devoted to the paleo-environment.…”
Section: Introductionmentioning
confidence: 99%